Cynical cosmopolitanism and its validity in the era of globalization (Iter, 2022)
The Cynic schoool of philosophy represented one of the most peculiar culturalmovements in Antiquity. The Cynic philosophers, like the street dogs thatgave them their name, were marginal figures in the society of the Greek poleis.However, they were the first to invent the idea of a “citizenship of the world”,i· e., a “cosmopolitism”. The aim of this paper is to study the Cynic concept ofcosmopolitism, with a view to determine its positive or negative value in thecontext of the mentality of the Hellenistic world, and to observe the similaritiesand differences between that ancient cosmopolitism and the idea of cosmopolitismthat emerges from our globalised world.
Keywords: cosmopolitism - Cynic philosophy - age of globalization